2013
DOI: 10.1093/nar/gkt864
|View full text |Cite
|
Sign up to set email alerts
|

The immediate upstream region of the 5′-UTR from the AUG start codon has a pronounced effect on the translational efficiency in Arabidopsis thaliana

Abstract: The nucleotide sequence around the translational initiation site is an important cis-acting element for post-transcriptional regulation. However, it has not been fully understood how the sequence context at the 5′-untranslated region (5′-UTR) affects the translational efficiency of individual mRNAs. In this study, we provide evidence that the 5′-UTRs of Arabidopsis genes showing a great difference in the nucleotide sequence vary greatly in translational efficiency with more than a 200-fold difference. Of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 54 publications
2
86
0
1
Order By: Relevance
“…This is compatible with previous findings that the 5 ′ UTR sequence near the start codon is significantly more unstructured than randomized sequences and other genomic regions (de Smit and van Duin 1990; Ringnér and Krogh 2005;Kudla et al 2009;Gu et al 2010;Goodman et al 2013;Kim et al 2014). Several recent experimental studies have confirmed the importance of reduced mRNA stability in the region near the start codon in the regulation of translation initiation and final gene expression (Dvir et al 2013;Kim et al 2014). Hence, we suggest that the 5 ′ UTR mRNA structure plays multiple roles in regulating post-transcriptional processes and that local mRNA secondary structure near the 5 ′ cap site, but not the structure of the full-length 5 ′ UTR, plays an important role in miRNA-mediated gene regulation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is compatible with previous findings that the 5 ′ UTR sequence near the start codon is significantly more unstructured than randomized sequences and other genomic regions (de Smit and van Duin 1990; Ringnér and Krogh 2005;Kudla et al 2009;Gu et al 2010;Goodman et al 2013;Kim et al 2014). Several recent experimental studies have confirmed the importance of reduced mRNA stability in the region near the start codon in the regulation of translation initiation and final gene expression (Dvir et al 2013;Kim et al 2014). Hence, we suggest that the 5 ′ UTR mRNA structure plays multiple roles in regulating post-transcriptional processes and that local mRNA secondary structure near the 5 ′ cap site, but not the structure of the full-length 5 ′ UTR, plays an important role in miRNA-mediated gene regulation.…”
Section: Discussionsupporting
confidence: 93%
“…The positive Z ΔG in the windows near the 3 ′ end of the 5 ′ UTR indicates that decreased mRNA stability is favored near the start codon. This is compatible with previous findings that the 5 ′ UTR sequence near the start codon is significantly more unstructured than randomized sequences and other genomic regions (de Smit and van Duin 1990; Ringnér and Krogh 2005;Kudla et al 2009;Gu et al 2010;Goodman et al 2013;Kim et al 2014). Several recent experimental studies have confirmed the importance of reduced mRNA stability in the region near the start codon in the regulation of translation initiation and final gene expression (Dvir et al 2013;Kim et al 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In Arabidopsis plants exposed to dehydration stress, transcripts that were better associated with polysomes during the stress were enriched in A nucleotides just upstream of the start codon . A recent study of Arabidopsis 5'UTRs further showed that the positions of A residues in the -1 to -5 region from the AUG were highly correlated with translational efficiency and uracil (U) residues in the same region were negatively correlated (Kim et al, 2014b). These results suggest that the region 5' to the AUG in Arabidopsis strongly influences translational efficiency in plants (Kim et al, 2014b).…”
Section: Start Site Recognitionmentioning
confidence: 96%
“…A recent study of Arabidopsis 5'UTRs further showed that the positions of A residues in the -1 to -5 region from the AUG were highly correlated with translational efficiency and uracil (U) residues in the same region were negatively correlated (Kim et al, 2014b). These results suggest that the region 5' to the AUG in Arabidopsis strongly influences translational efficiency in plants (Kim et al, 2014b). mRNAs with a 5'UTR that was shorter than average (125 nt) and had low potential for secondary structure formation had higher levels of ribosome occupancy.…”
Section: Start Site Recognitionmentioning
confidence: 99%